50 Portomesenteric venous thrombosis as an indication for intestinal or multivisceral transplantation. (5th April 2017) - McKenna, C; Dunne, C; Yeap, S; Butler, A; Russell, N; Massey, D; Middleton, S; Woodward, J; Sharkey, L
Abstract : Introduction: The established indications for Intestinal and Multivisceral (MVT) transplant include IFALD, loss of vascular access and recurrent line sepsis. Aim: Over the last four years there have been an increasing number of patients with portomesenteric venous thrombosis (PMVT) referred some of whom are not cirrhotic. Method: Data was collected on all patients who underwent Intestinal or MVT between 2006 and 2013 in Addenbrooke's hospital, Cambridge and was then divided into pre 2013 and post 2013. Results: Over the last 8 years there were 73 transplants in 67 patients. Between 2006 and 2013 there were 30 transplants compared to 43 transplants since 2013. Short gut syndrome remains the largest indication for transplant with 16 (53%) transplants between 2006 and 2013 and 22 (51%) transplants from 2013. Prior to 2013 only 3 patients had undergone multivisceral transplant for cirrhosis complicated by PMVT. Since 2013 there have been 8 transplants for cirrhosis complicated by PMVT. Five of these were multivisceral transplants while three underwent a liver-small bowel transplant. In 2016 two patients with PMVT not complicated by cirrhosis underwent isolated Intestinal transplants. One patient required a Whipple procedure but was unable to have this due to PMVT. The other patient had recurrent bleeding with PMVT not amenable to conventional therapy. Conclusions: While the established indications for Intestinal or MVT remain, there has been an increase in the number of transplants performed for cirrhotic patients with PMVT in which an isolated liver transplant is precluded.